PENGARUH EMPLOYER BRANDING ACTIVITY DAN CORPORATE REPUTATION TERHADAP INTENTION TO APPLY FOR A JOB - Kartika, Rizkitania Citra; Riandi, Muhammad Hafiz (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research departs form the war of talent, a phenomenon of diminishing number of potential work forces occurring in various industries. As a response, companies are competing to attract employee candidates to apply for jobs. The objective of this research is to identify the partial and simultaneous effects of employer branding activity and corporate reputation on people’s intention to apply for a job. The population of this quantitative explanatory research is active students of bachelor’s and associate degrees of Universitas Brawijaya. Using the Slovin formula, the sample size was set at 398. The data was harvested via Likert-scaled questionnaires and was assessed using instrument test, classical assumption test, hypothesis test, and multiple linear regression performed in SPSS. This study finds that employer branding activity and corporate reputation partially and simultaneously influence the intention to apply for a job. Therefore, it is implied that appropriate strategies in employer branding activity and successful corporate reputation maintenance can increase the intention of employee candidates to apply for a job.